In search of the best candidate for regeneration of ischemic tissues - Emanueli, Costanza; Lako, Majlinda; Stojkovic, Miodrag; Madeddu, Paolo (Thrombosis and Haemostasis, 2005)
Human stem cells and progenitor cells from the bone marrow have been proposed for the regeneration of ischemic cardiac tissues. Early clinical trials indicate that infusion of autologous bone-marrow cells into the infarcted heart enhances ventricular function, albeit the long-term benefit remains to be ascertained. Alternatively, angiogenic growth factors could be used to stimulate the recruitment of vascular progenitor cells into tissues in need of regeneration. Unfortunately, in atherosclerotic patients, the curative potential of autologous stem cells might be impoverished by underlying disease and associated risk factors. Thus, research is focusing on the use of embryonic stem cells which are capable of unlimited self-renewal and have the potential to give rise to all tissue types in the body. Ethical problems and technical hurdles may limit the immediate application of embryonic stem cells. In the meanwhile, fetal hematopoietic stem cells, which have been routinely used to reconstitute the hematopoietic system in man, could represent an alternative, owing to their juvenile phenotype and ability to differentiate into vascular endothelial, muscular, and neuronal cell lineages. With progresses in stem cell expansion, the blood of a single cord could be sufficient to transplant an adult. These observations raise the exciting possibility of using fetal cells as a new way to speed up the healing of damaged tissues.This study was partially supported by the Italian Health Institute (Stem Cell Program).
Keywords: Angiogenesis; vasculogenesis; ischaemic heart disease; fetal progenitor cells; nuclear transfer